Hypertensive patients: self-care experience in rural community - Susanto, Joko; Makhfudli, Makhfudli; Ilkafah, Ilkafah; Tyas, Anestasia Pangestu Mei; Yusuf, Ah.; Iswatun, Iswatun (International Journal of Public Health Science (IJPHS), 2025)
Hypertension is a chronic disease that often occurs in the world. Individual involvement in self-care is very important, in controlling blood pressure. The inability to carry out treatment will increase the risk and complications. The aim study is to explore the experiences and behavior of self-management and self-care of hypertension patients. The study is qualitative research with a phenomenological approach. The technique for taking participants was a purposive sampling of ten hypertensive patients. Data was collected using semi-structured interviews and then analyzed thematically based on the methodological framework of constructivist basic theory. Participant statements describing patient experiences in self-care include six themes, namely the cause of recurrences, emotional response, social support, self-care behavior, barriers to self-care, access to health facilities. The support factors of social support from family, health workers, and affordability of health services greatly influence self-care. An adequate support system, especially from nurses, is needed by patients because it will increase active participation so that patients will try to improve their care and skills in self-care.